2019
DOI: 10.18203/2320-6012.ijrms20193921
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C based eGFR - for early detection of diabetic kidney disease

Abstract: Background: Diabetic kidney disease is the leading cause of premature death in young diabetic patients. Detection of diabetic kidney disease as early as possible in the disease process currently offers the best chance of delaying or possibly preventing progression to end-stage renal disease. The present study was aimed to evaluate utility of serum cystatin C based eGFR for early diagnosis of diabetic kidney disease.Methods: Diagnosed patients of type 2 diabetes mellitus having frank proteinuria were excluded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The use of triangular pipes allowed to increase the temperature of the water at the outlet. Authors of [1] compared round and elliptical pipes and found that the round pipe provides the maximum temperature of the water at the outlet with the same heat flux and inlet temperature. Numerical methods based on CFD (computational fluid dynamics) models are used to analyze phenomena occurring in solar collectors.…”
Section: Introductionmentioning
confidence: 99%
“…The use of triangular pipes allowed to increase the temperature of the water at the outlet. Authors of [1] compared round and elliptical pipes and found that the round pipe provides the maximum temperature of the water at the outlet with the same heat flux and inlet temperature. Numerical methods based on CFD (computational fluid dynamics) models are used to analyze phenomena occurring in solar collectors.…”
Section: Introductionmentioning
confidence: 99%